Wind Erosion Control by Liquefied Corn Stalk as a Novel Sand-Fixing Agent - Wang, T.P.; Zheng, Z.M. (Asian Journal of Chemistry, 2012)
Liquefied corn stalk was evaluated as a sand fixation agent for wind erosion control. Experiments were conducted in a wind tunnel on two representative soil samples, the severely eroded dune soil and the cultivated soil. Results showed that liquefied corn stalk application on the soil surfaces led to the formation of crust and the increase of soil threshold wind velocity and the decrease of the wind erosion rate. At an liquefied corn stalk cover density of 148 g/m2, the threshold wind velocity improved from 6 to up to 20 m/s for the cultivated soil and from 4.8 to 14.6 m/s for the dune soil at an liquefied corn stalk cover density of 138 g/m2. It was concluded that liquefied corn stalk is a promising sand fixation material for both cultivated soil and the dune soil for wind erosion control.